A FAM21-Containing WASH Complex Regulates Retromer-Dependent Sorting - Gomez, Timothy S. (2009)
The Arp2/3 complex regulates endocytosis, sorting and trafficking, yet the Arp2/3-stimulating factors orchestrating these distinct events remain ill-defined. WASH (Wiskott-Aldrich Syndrome Protein and SCAR Homolog) is an Arp2/3 activator with unknown function that was duplicated during primate evolution. We demonstrate that WASH associates with tubulin and localizes to early endosomal subdomains, which are enriched in Arp2/3, F-actin, and retromer components. While WASH localized with activated receptors, it was not essential for endocytosis. However, WASH did regulate retromer-mediated retrograde CI-MPR trafficking, which required its association with endosomes, Arp2/3-directed F-actin regulation and tubulin interaction. Moreover, WASH exists in a multi-protein complex containing FAM21, which links WASH to endosomes and is required for WASH-dependent retromer-mediated sorting. Significantly, without WASH, retromer tubulation was exaggerated supporting a model wherein WASH links retromer-mediated cargo containing tubules to microtubules for Golgi-directed trafficking and generates F-actin-driven force for tubule scission.